Farm Animal Transport - Weeks, Claire A. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Most of the 70 billion animals that are farmed in the world are transported at least once in their lives. For improved animal welfare, sustainability, and profitability it is important that everyone involved in the transportation process takes responsibility for doing a good job. This may require legislation and assurance schemes backed up by inspections and driven by consumer awareness and demand. All aspects of the transportation process, including preparation for transport, handling during loading and unloading, handler and driver training, stocking density on the transport container, journey length, and weather have an effect on animal welfare, meat quality, health after transport, and even mortality during transit. These topics are covered in the papers and reviews in this book together with related aspects such as consumer perceptions of animal transport, cleaning of transport coops, and consideration of on-farm slaughter to obviate the need for transport to an abattoir. The book adds to the knowledge of farm animal transport and highlights areas for future research and improved practice.